Percepciones sobre salud (física, mental y bucal) en un grupo de mujeres en situación de prostitución en la ciudad de Medellín (2023)
ABSTRACT: Introduction: women and trans people who have engaged in sex work are triply vulnerable since they are victims of discrimination due to their employment status, their gender, and the risks that this work entails, this impacts their health situation. This study aimed to know the perceptions about health (physical, mental, and oral) of four women who work in prostitution in Medellin, based on their life experiences and those related to their social context. Methods: qualitative research with an ethnographic approach was conducted to analyze the situations mentioned. Four women participated, two Venezuelans and two Colombians, and semi-structured interviews were conducted. Qualitative content analysis was performed, which allowed the generation of four categories (mental health, oral health, general health, and quality of life). Results: her discourses made it possible to elucidate the connection between the living conditions and the health situation. Lack of job opportunities, a migratory process of profound economic and social changes, and a Colombia with inequities and barriers to access to health and social services are determining processes of a general and singular order of the precarious conditions of oral health and general. Conclusions: the participating population is in a situation of social and health vulnerability, which shows the need for public policies and strategies based on the social reality that contribute to generating equity in health.